Cancer Immune Therapy 2002
DOI: 10.1002/3527600795.ch9
|View full text |Cite
|
Sign up to set email alerts
|

Dendritic Cells and Cancer: Prospects for Cancer Vaccination

Abstract: Effective therapeutic cancer vaccination is an old dream, now rekindled by modern advances in cell biology and immunology. Several key facts have inspired the current optimism for clinical immunotherapy trials. First, the realization that, by definition, every malignant cell must express at least one gene product in an abnormal fashion means that theoretically there is at least one tumor-associated antigen (TAA) (it may be an autoantigen) available as a target. Secondly, we now know that any cellular protein (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2006
2006
2008
2008

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 107 publications
0
1
0
Order By: Relevance
“…Dendritic cells (DC) are professional antigen-presenting cells for activation of antigen-specific CTL, which underlies effective cancer immunotherapy. Dendritic cells are responsible for processing and presenting human leukocyte antigen (HLA)-restricted peptide epitopes to CD8+ T cells through the major histocompatibility complex (MHC)-I pathway . Recently, one of us reported that intranodal injection of dendritic cells ex vivo pulsed with a HLA-A11 restricted LMP-2 epitope (SSCSSCPLSK) induced EBV specific CTL in vivo, and regression of metastatic tumor in selected NPC patients has been observed .…”
Section: Introductionmentioning
confidence: 99%
“…Dendritic cells (DC) are professional antigen-presenting cells for activation of antigen-specific CTL, which underlies effective cancer immunotherapy. Dendritic cells are responsible for processing and presenting human leukocyte antigen (HLA)-restricted peptide epitopes to CD8+ T cells through the major histocompatibility complex (MHC)-I pathway . Recently, one of us reported that intranodal injection of dendritic cells ex vivo pulsed with a HLA-A11 restricted LMP-2 epitope (SSCSSCPLSK) induced EBV specific CTL in vivo, and regression of metastatic tumor in selected NPC patients has been observed .…”
Section: Introductionmentioning
confidence: 99%